2019
DOI: 10.1002/ajmg.b.32736
|View full text |Cite
|
Sign up to set email alerts
|

International Society of Psychiatric Genetics Ethics Committee: Issues facing us

Abstract: Psychiatric genetics research is improving our understanding of the biological underpinnings of neurodiversity and mental illness. Using psychiatric genetics in ways that maximize benefits and minimize harms to individuals and society depends largely on how the ethical, legal, and social implications (ELSI) of psychiatric genetics are managed. The International Society of Psychiatric Genetics (ISPG) is the largest international organization dedicated to psychiatric genetics. Given its history, membership, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 115 publications
0
13
0
Order By: Relevance
“…As some of us (G.L.-M.) together with the ISPG Ethics Committee have noted recently, there is a pressing need for research examining the impact of RoR on these participants. 31 Little to no information is currently exchanged among researchers to help identify quality-controlled procedures to prevent or reduce harm to psychiatric participants with special needs. [32][33][34][35][36] Significant gaps exist in the literature reporting researchers' experiences with RoR and impacts of specific RoR procedures on recipients' well-being.…”
Section: Discussionmentioning
confidence: 99%
“…As some of us (G.L.-M.) together with the ISPG Ethics Committee have noted recently, there is a pressing need for research examining the impact of RoR on these participants. 31 Little to no information is currently exchanged among researchers to help identify quality-controlled procedures to prevent or reduce harm to psychiatric participants with special needs. [32][33][34][35][36] Significant gaps exist in the literature reporting researchers' experiences with RoR and impacts of specific RoR procedures on recipients' well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Using genetics to maximize the benefits and minimize the harms to individuals and society requires the effective management of the ethical, legal, and social implications of genetics. Researchers have a responsibility to ensure that the technology and the knowledge developed through genetic research are used responsibly, in light of the bioethical principles of beneficence, non-maleficence, justice, and autonomy (Lázaro-Muñoz et al, 2019). Given that for most complex disorders there is currently a lack of data regarding the harms or benefits of accessing PRS information, the fundamental principle in favor of making PRSs available to the public is that of autonomy-in the context of genetic testing, this refers to "the right of persons to make an informed, independent judgment about whether they wish to be tested and then whether they wish to know the details of the outcome of the testing" (Andrews et al, 1994).…”
Section: Ethics and Implicationsmentioning
confidence: 99%
“…If present, these symptoms could increase the likelihood of participants misunderstanding the implications of results or having a negative emotional response. There is, however, a dearth of research about the impact of returning results to individuals at risk for psychiatric disorders or who have a psychiatric diagnosis [13]. One of the few relevant studies found that individuals with depressive symptoms who were told that they were at an increased genetic risk for depression were more likely to believe they were currently experiencing major depression or would experience it in the future ("prognostic pessimism") compared to people with depressive symptoms told they were not at an increased genetic risk for depression [14].…”
Section: Introductionmentioning
confidence: 99%